Present status of fish culture in daulatabad talaw(amrai talaw) dist- Aurangabad (M.S.), India - Jadhav, T J; Gaikawad, B H; Hafhiz, Shaikh; Shaikh, J D (International Multidisciplinary Research Journal, 2012)
Present study is give to fish culture status, production and development of talaw. An attempt has been made to involve present status for fishery culture improvement in the management and commercial production of the fishes. It controlled by private agency.